2014
DOI: 10.1002/ar.23069
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Geometric Morphometric Analysis of Talar Morphology in Extant Gorilla Taxa from Highland and Lowland Habitats

Abstract: Western gorillas (Gorilla gorilla) are known to climb significantly more often than eastern gorillas (Gorilla beringei), a behavioral distinction attributable to major differences in their respective habitats (i.e., highland vs. lowland). Genetic evidence suggests that the lineages leading to these taxa began diverging from one another between approximately 1 and 3 million years ago. Thus, gorillas offer a special opportunity to examine the degree to which morphology of recently diverged taxa may be "fine-tune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
78
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(98 citation statements)
references
References 74 publications
13
78
1
Order By: Relevance
“…Future studies with increased samples (per species) should also focus on locomotor differences between congeneric species (e.g., the more arboreal Gorilla gorilla versus the more terrestrial Gorilla beringei) to see if morphological differences in the distal MT correspond to observed differences in the positional behavior (e.g., Doran, 1996Doran, , 1997Doran and McNeilage, 1998) between these two species. There is a long standing and growing body of morphological literature that demonstrates significant anatomical differences between gorilla species (Schultz, 1930(Schultz, , 1934Sarmiento, 1994;Harcourt-Smith, 2002;Tocheri et al, 2011;Dunn et al, 2014;Knigge et al, 2015), and an assessment of the distal metatarsus focused on gorilla species may lend additional support to this line of research. Finally, the distal half of the metatarsophalangeal jointsdthe proximal phalangeal base articular surfacedshould also be quantified using methods similar to those applied in the present study in order to provide a context for the analysis of proximal phalanges in the hominin fossil record.…”
Section: Discussionmentioning
confidence: 95%
“…Future studies with increased samples (per species) should also focus on locomotor differences between congeneric species (e.g., the more arboreal Gorilla gorilla versus the more terrestrial Gorilla beringei) to see if morphological differences in the distal MT correspond to observed differences in the positional behavior (e.g., Doran, 1996Doran, , 1997Doran and McNeilage, 1998) between these two species. There is a long standing and growing body of morphological literature that demonstrates significant anatomical differences between gorilla species (Schultz, 1930(Schultz, , 1934Sarmiento, 1994;Harcourt-Smith, 2002;Tocheri et al, 2011;Dunn et al, 2014;Knigge et al, 2015), and an assessment of the distal metatarsus focused on gorilla species may lend additional support to this line of research. Finally, the distal half of the metatarsophalangeal jointsdthe proximal phalangeal base articular surfacedshould also be quantified using methods similar to those applied in the present study in order to provide a context for the analysis of proximal phalanges in the hominin fossil record.…”
Section: Discussionmentioning
confidence: 95%
“…Many investigators have stressed the importance of foot inversion (and dorsiflexion) during vertical climbing in nonhuman hominoids (DeSilva, ; Holowka, O'Neill, Thompson, & Demes, ; Wunderlich & Ischinger, ; and see Figure b). Anatomical correlates of this behavior have been documented in the talus of G. g. gorilla compared to that of G. b. beringei , which is better adapted for more sagittally‐constrained terrestrial loadings (Dunn, Tocheri, Orr, & Jungers, ; Knigge et al, ). Foot inversion during climbing is combined with knee flexion and hip abduction and flexion, which displaces the knee laterally (Figure b) (Isler, ; Neufuss, Robbins, Baeumer, Humle, & Kivell, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we compare the same parameters with age‐matched samples of wild Virunga Gorilla beringei beringei (Eastern mountain gorillas). Adult G. b. beringei are more terrestrial than adult G. g. gorilla (Doran, , ; Doran‐Sheehy, Andrianady, & Lodwick, ; Knigge, Tocheri, Orr, & Mcnulty, ; Masi, ; Remis, , , ; Ruff et al, , ; Schaller, ). Because opportunities for natural behavior in captive environments are generally more limited and can reflect substrate complexities (Ross, Schapiro, Hau, & Lukas, ; Ross et al, ), we predict that where adult wild G. g. gorilla and G. b. beringei differ in morphology, captive adult G. g. gorilla will more closely resemble the more terrestrial G. b. beringei .…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that hominid talar shape varies between groups characterized by different locomotor modes and substrate uses (Dunn, Tocheri, Orr, & Jungers, ; Knigge, Tocheri, & Orr, ; Turley, ; Turley & Frost, , ; Turley, White, & Frost, ). However, less is known about variation in talar morphology within modern humans (Harcourt‐Smith, ; Saers et al, ; Turley, ; Turley et al, ).…”
Section: Introductionmentioning
confidence: 99%